Adenoviral vaccine targeting multiple neoantigens as strategy to eradicate large tumors combined with checkpoint blockade - Anna Morena D’Alise (Nature Portfolio, 2019)
Vaccination against neo-antigens has resulted in an effective antitumor response in several models. Here, the authors show that delivery of larger sets of neo-antigens using an adenovirus-based vaccination platform, results in much better tumor protection when combined with checkpoint blockade in a mouse model of advanced disease.